A Comparative Study of the Saudi Insurance Legal Environment with the International Insurance Environment – An Empirical Study - AlNemer, Hashem A. (Archives of Business Research, 2016)
This paper will provide an overview of the insurance industry in Saudi Arabia and the regulatory instruments that operate under the Saudi Arabian Monetary Agency (SAMA), with a brief on the situations of the licensed insurance companies in the Kingdom. The current paper will also provide information and data on the Saudi insurance market growth rate and financial performance. Importantly, this paper compares the Saudi insurance regulatory laws and directives with the international insurance one and takaful standards and policies with participants’ perceptions. No studies have been conducted to systematically compare SAMA’s regulations and standards for insurance with an international one. Such comparisons provide an efficient framework for better protections for policyholders. This paper attempts to fill the gap. Distributing survey questioners among takaful participants is another vital approach for this paper. The paper reports results on the perceptions of 420 participants of takaful companies in Saudi Arabia. They were asked in away to figure out if the current directives imposed by SAMA have enough protections towards participants. Protections might occur by enhancing participants’ knowledge, perceptions and satisfaction through obligatory disclosure rules of the TOs (takaful operators). A conclusion can be made that SAMA, does not have any directives and laws towards the takaful business, nor does it issue directives that address any Shari’ah concerns. Accordingly, it is highly recommended that SAMA assigns separate directive laws that address the takaful insurance, and the principles of the Shari’ah laws. It is also recommended that SAMA enhances their employees’ knowledge about the principles and products of the takaful model. SAMA should also rely on the already-established standards as per AAOIFI, IFSB and similar standards as per IAIS to regulate the takaful insurance in Saudi Arabia